Analysing the Legal and Regulatory Framework of Technology Transfer Regimes in Developing Countries : The case of Ghana - Kabre, Rimdolmsom Jonathan (University of Pretoria, 2021)
Mini Dissertation (LLM (International Trade and Investment law in Africa))--University of Pretoria ,2021.